Peran Kepala Sekolah sebagai Agen Perubahan dalam Meningkatkan Kinerja Organisasi Pendidikan: Studi Kasus Manajemen Perubahan di SMAN 1 Siluq Ngurai, Kabupaten Kutai Barat - Friska Umi Puspita Sari; Irmawati; M. Guntur; Warman; Dwi Nugroho Hidayanto; Muhammad Amir Masruhim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the principal’s role as a change agent in improving organizational performance at SMAN 1 Siluq Ngurai, Kutai Barat Regency. Employing a qualitative approach with a case study method, the research explores the processes, strategies, and dynamics of change through in-depth interviews, observations, and document analysis. The findings reveal that the principal implemented several key strategies, including administrative digitalization, regular teacher training, the establishment of a collaborative culture, and data-driven school governance. The results indicate significant improvements in administrative efficiency, enhanced teacher pedagogical competence, and strengthened instructional innovation. Furthermore, the school’s organizational performance scores increased consistently from 2021 to 2024, demonstrating the principal’s success in embedding change within the school’s culture and management system. This study confirms that visionary and adaptive change leadership is essential for successful educational transformation, particularly in schools located in resource-limited areas.